Nursing care of patients with diabetes complications qualify to pancreatic islet transplantation - Hreńczuk, Marta; Wszoła, Michał; Pszenny, Anna; Berman, Andrzej; Chmura, Andrzej; Małkowski, Piotr (Nursing Problems / Problemy Pielęgniarstwa, 2012)
There are 2,5 million diabetics in Poland. Isolation of insulin in 1921 gave a possibility to prolong diabetic’s life however many complications, such as: nephropathy, retinopathy, micro and macroangiopathy may occur. The program of pancreas transplantation was a turning point in diabetes treatment. Pancreatic islet transplantation is an alternative method for patients non suitable for surgical treatment due to cardiological complications. The aim of this paper was to define health problems of patients with diabetes complications qualified to pancreatic islet allotransplantation. Pancreatic islet allotransplantation is performed in type 1 diabetes. Patients considered for this treatment must suffer from diabetes for at least 5 years and the level of peptic C should be below 0.05 ng/ml. Patients are divided into 3 groups: 1. non stable diabetes, hypoglycemia and nephropathy; 2. nephropathy with renal failure; 3. nephropathy and immunosupression complications after kidney transplantation. In the first group problems related with hypoglycaemic episodes are dominant. Main concern in the second group is developing kidney insufficiency. Major problem In the third is immunosupression applied after kidney transplantation. Patients who have been suffering from diabetes for at least 5 years are considered to pancreatic islet allotransplantation. They are a special group of patients with many specific complications and they need a professional nursing care.